2010
DOI: 10.1016/j.freeradbiomed.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic considerations for the reaction of semiquinone radicals to form superoxide and hydrogen peroxide

Abstract: The quinone/semiquinone/hydroquinone triad (Q/SQ •− /H 2 Q) represents a class of compounds that has great importance in a wide range of biological processes. The half-cell reduction potentials of these redox couples in aqueous solutions at neutral pH, E°′, provide a window to understanding the thermodynamic and kinetic characteristics of this triad and their associated chemistry and biochemistry in vivo. Substituents on the quinone ring can significantly influence the electron density "on the ring" and thus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
291
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(325 citation statements)
references
References 135 publications
17
291
1
9
Order By: Relevance
“…24,25 It is found that the pK a values of hydroquinone are much bigger than that of the semiquinone while E Q/Q•− and E Q•−/Q2− are similar; normally the pK a of QH…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 It is found that the pK a values of hydroquinone are much bigger than that of the semiquinone while E Q/Q•− and E Q•−/Q2− are similar; normally the pK a of QH…”
Section: -mentioning
confidence: 99%
“…It is deemed that the primary mechanism of highly toxic superoxide generation via quinone compounds involves the semiquinone radical. 25,46 Autoxidation of hydroquinones by O 2 is known to be catalyzed by Q ox , because Q ox can produce Q sem by reacting with hydroquinone, Q red . In the Q cycle of mitochondria, it is very difficult to observe the semiquinone radical at the Q o site, which probably acts to suppress superoxide generation.…”
mentioning
confidence: 99%
“…6b). HT-quinone may interact with HT in a comproportionation reaction to generate more semiquinone radicals (Song and Buettner 2010;Song et al 2008;Song et al 2009). This redox cycle of HT could elicit an oxidative stress response and cells may adapt to this oxidative insult by promoting their antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…6a). Semiquinone radicals are the primary source for formation of superoxide from the hydroquinonesemiquinone-quinone triad (Eyer 1991;Song and Buettner 2010;Song et al 2008;Venkatesha et al 2008). If superoxide is formed in the oxidation of hydroquinones that have relatively high redox potentials, then superoxide dismutase will accelerate the oxidation of hydroquinone, forming quinone.…”
Section: Sodium Cyanide Was Used To Distinguish Between Mnsod and Cuzmentioning
confidence: 99%
“…Reoxidation of these agents requires strong oxidizing systems such as the cytochrome P450's so that toxicity is limited to metabolizing organs such as liver and kidney. [55,63,64] …”
Section: Redox Agentsmentioning
confidence: 99%